2022
DOI: 10.5534/wjmh.210191
|View full text |Cite
|
Sign up to set email alerts
|

Post-Vasectomy Semen Analysis: Optimizing Laboratory Procedures and Test Interpretation through a Clinical Audit and Global Survey of Practices

Abstract: Purpose The success of vasectomy is determined by the outcome of a post-vasectomy semen analysis (PVSA). This article describes a step-by-step procedure to perform PVSA accurately, report data from patients who underwent post vasectomy semen analysis between 2015 and 2021 experience, along with results from an international online survey on clinical practice. Materials and Methods We present a detailed step-by-step protocol for performing and interpretating PVSA testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Table 2 [ 3 22 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 ] illustrates that 23 articles were published in prestigious peer-reviewed journals by author contributions representing 46 countries. Broadly classified, these articles tackled contemporary challenges in andrology spanning across topics of sperm DNA damage, semen analysis, laboratory issues in relation to assisted reproductive technique (ART), sperm recovery, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 [ 3 22 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 ] illustrates that 23 articles were published in prestigious peer-reviewed journals by author contributions representing 46 countries. Broadly classified, these articles tackled contemporary challenges in andrology spanning across topics of sperm DNA damage, semen analysis, laboratory issues in relation to assisted reproductive technique (ART), sperm recovery, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Even with this caveat, the vast majority of UC patients in our study (> 98%) have either a known vasectomy date or recorded postvasectomy semen analysis, which usually occurs around 3 months after a vasectomy. 51 Moreover, vasectomy patients were chosen for their presumptive fertility, as previous studies have shown that 90% of patients seeking a vasectomy are fertile. 12 Thus, that the precise date of vasectomy may be unknown may not have a meaningful impact on our findings.…”
Section: Discussionmentioning
confidence: 99%
“…There are several surgical techniques for vasectomy, 4 but whatever the approach, it is necessary to verify the absence of ejaculated spermatozoa to guarantee sterility because of spermatozoa storage on the abdominal side of the ligation site and the potential for recanalization of the cut ends of the vas deferens 4,6 …”
Section: Introductionmentioning
confidence: 99%
“…5 There are several surgical techniques for vasectomy, 4 but whatever the approach, it is necessary to verify the absence of ejaculated spermatozoa to guarantee sterility because of spermatozoa storage on the abdominal side of the ligation site and the potential for recanalization of the cut ends of the vas deferens. 4,6 Postvasectomy semen analyses are routinely ordered by surgeons performing the vasectomy, but patient compliance is low, ranging from 58% to 75%. 7,8 The 2002 British Andrology Society guidelines recommended three postvasectomy semen analyses: two within several weeks of the procedure and a third at 1 year to rule out re-canalization.…”
Section: Introductionmentioning
confidence: 99%